Drosophila C-terminal binding protein, dCtBP is required for sensory organ prepattern and sharpens proneural transcriptional activity of the GATA factor Pnr. - Biryukova, I.; Heitzler, P. (Developmental Biology, 2008)
The peripheral nervous system is required for animals to detect and to relay environmental stimuli to central nervous system for the information processing. In Drosophila, the precise spatial and temporal expression of two proneural genes achaete (ac) and scute (sc), is necessary for development of the sensory organs. Here we present an evidence that the transcription co-repressor, dCtBP acts as a negative regulator of sensory organ prepattern. Loss of dCtBP function mutant exhibits ectopic sensory organs, while overexpression of dCtBP results in a dramatic loss of sensory organs. These phenotypes are correlated with mis-emerging of sensory organ precursors and perturbated expression of proneural transcription activator Ac. Mammalian CtBP-1 was identified via interaction with the consensus motif PXDLSX(K/R) of adenovirus E1A oncoprotein. We demonstrated that dCtBP binds directly to PLDLS motif of Drosophila Friend of GATA-1 protein, U-shaped and sharpens the adult sensory organ development. Moreover, we found that dCtBP mediates multivalent interaction with the GATA transcriptional activator Pannier and acts as a direct co-repressor of the Pannier-mediated activation of proneural genes. We demonstrated that Pannier genetically interacts with dCtBP-interacting protein HDAC1, suggesting that the dCtBP-dependent regulation of Pannier activity could utilize a repressive mechanism involving alteration of local chromatine structure.